Case Report: A case report of myocardial fibrosis activation assessment after unstable angina using 68Ga-FAPI-04 PET/CT - Jiang, Mimi; Zhang, Guolan; Li, Le; He, Yuanyuan; Li, Guo; Yu, Jinmei; Feng, Jian; Liu, Xing (Frontiers in Cardiovascular Medicine, 2024)
Myocardial ischemia may induce myocardial fibrosis, a condition that progressively leads to ventricular remodeling, heightening the risk of heart failure. The timely detection of myocardial fibrosis is crucial for intervention and improved outcomes. 68 Ga-FAPI-04 PET/CT shows promise in assessing fibroblast activation in patients with early myocardial infarction characterized by prolonged myocardial ischemia. However, there is a notable absence of data regarding patients with short-term myocardial ischemia, such as those experiencing unstable angina (UA). In this report, we evaluated a 49-year-old male with UA and severe stenosis in multiple coronary arteries using 68 Ga-FAPI-04 PET/CT. The results demonstrated tracer-specific uptake (SUVmax=4.6) in the left anterior descending artery (LAD) territory, consistent with myocardial anterior wall ischemia indicated by the electrocardiogram. Following vascular recanalization therapy and regular medication treatment, the patient remained free of angina recurrence. A subsequent review at 2 months revealed a significant reduction in myocardial tracer uptake (SUVmax=1.8). This case illustrates the validity of 68 Ga-FAPI-04 PET/CT in assessing the extent of early myocardial fibroblast activation in patients with UA. This approach offers valuable insights for early detection and visual evidence, providing information on disease progression and treatment response.